PISA 2022 Norske elevers kompetanse i matematikk, naturfag og lesing - Jensen, Fredrik (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2023)
PISA (Programme for International Student Assessment) is an international, comparative survey of 15-year-olds' competence in mathematics, science and reading. The purpose of the PISA survey is to assess how well students are prepared, by the end of compulsory education, to use their skills and knowledge in these three subject areas in further studies, working life and private life. The survey facilitates analysing changes in the results over time and comparing results from different countries. From a Norwegian perspective, it is particularly interesting to look at similarities and differences between the Nordic countries. The PISA survey is part of a larger quality assessment system. That is to say, the PISA program is one of several sources of information utilized in assessing the quality of Norwegian schools. PISA surveys have been conducted every three years since 2000, with the exception of the 2021 survey, which was postponed until 2022 due to the COVID-19 pandemic. This report presents the first results from the eighth iteration of the survey, PISA 2022, in which mathematics was the primary subject area. The report has been written for a general audience, in addition to school administrators, teachers, teaching students and others concerned with the state of Norwegian secondary school education.